Moderasi Brand Image pada Digital Marketing dan E-Service Quality Terhadap Minat Konsumen Difcloth Samarinda - Ermi Utami; Achmad Akbar; Mursidah Nurfadillah (Universitas Muhammadiyah Jambi, 2024)
This research aims to analyze the influence of Digital Marketing and E-Service Quality on consumer buying interest in Difcloth Samarinda with Brand Image as a moderating variable. This type of research is quantitative research, the objects used are Difcloth Samarinda consumers who are Instagram followers @difcloth _. The population in this study was all 4,400 Instagram followers @difcloth_ and the sampling technique used was simple random sampling where in calculations using the Slovin formula, 98 respondents were obtained. The data collection technique uses a questionnaire and is calculated using a Likert scale. The analysis tool uses multiple linear regression with moderation. The data collection techniques used were interviews, questionnaires and observation. The data analysis techniques used in this research are multiple linear regression analysis, validity test, reliability test, normality test, multiconference test, heteroscedasticity test, t test, f test, and coefficient of determination with the help of the SPSS program. The research results show that (1) digital marketing has a positive and significant effect on consumer purchasing interest in difcloth, (2) e-service quality has a positive and significant effect on consumer purchasing interest in difcloth, (3) Brand image strengthens the influence of digital marketing & e-service quality on consumer interest in difcloth. Keywords: Digital Marketing, E-Service Quality, Instagram, Brand Image.